2022
DOI: 10.1021/acs.iecr.2c00452
|View full text |Cite
|
Sign up to set email alerts
|

Developing Benign Ni/g-C3N4 Catalysts for CO2 Hydrogenation: Activity and Toxicity Study

Abstract: This research discusses the CO 2 valorization via hydrogenation over the non-noble metal clusters of Ni and Cu supported on graphitic carbon nitride (g-C 3 N 4 ). The Ni and Cu catalysts were characterized by conventional techniques including XRD, AFM, ATR, Raman imaging, and TPR and were tested via the hydrogenation of CO 2 at 1 bar. The transition-metal-based catalyst designed with atom-economy principles presents sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…All of the samples revealed a hump peak at 25.9°, which is compatible with the g-C 3 N 4 characteristic peak, which may be ascribed to the MCN (002) reflection plane 64 . This peak, in particular, is indicative of MCN's graphitic origin because it is a characteristic of graphitic materials 58 . As a consequence, because it is allocated from the planes generated by the agglutination of the connected aromatic groups in the layered structure, it is evidence of MCN and graphene's layered structural similarities 65 , 66 .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…All of the samples revealed a hump peak at 25.9°, which is compatible with the g-C 3 N 4 characteristic peak, which may be ascribed to the MCN (002) reflection plane 64 . This peak, in particular, is indicative of MCN's graphitic origin because it is a characteristic of graphitic materials 58 . As a consequence, because it is allocated from the planes generated by the agglutination of the connected aromatic groups in the layered structure, it is evidence of MCN and graphene's layered structural similarities 65 , 66 .…”
Section: Resultsmentioning
confidence: 94%
“…Substantial studies on CO 2 thermal methanation employing monometallic nickel-doped mesoporous carbon nitride revealed low performance, needing more inquiry and development to reach the greatest CO 2 conversion Percentage as well as flawless CH 4 selectivity. Izabela S. Pieta et al study's exemplifies ongoing research into the performance of Ni-doped carbon nitride in CO 2 methanation 58 . According to Izabela S. Pieta et al, under atmospheric pressure, CO 2 conversion and selectivity for light hydrocarbons, such as methane, increase as the temperature rises.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Researchers have devised a variety of CO 2 reduction strategies, including thermochemical [2] , electrochemical [3] , and photochemical methods [4] . Methanol, carbon monoxide, ethylene, and other compounds can be produced from CO 2 [5] , [6] , [7] But the development of catalysts for CO 2 photo-reduction is still lagging due to a lack of effective, reliable, cost-effective, and highly selective catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing now on CO 2 transformation using green hydrogen, Tsubaki et al reported the direct conversion of CO 2 to aromatics using a bifunctional zeolite-based catalyst, Herskovitz et al. investigated the process configuration and technoeconomic aspect of CO 2 hydrogenation to renewable liquid fuels, Fan et al reported the conversion of CO 2 to light olefins using metal oxides, Pieta et al discussed the conversion of CO 2 to CO and methane using non-noble-metal-supported catalysts, Wang et al reported the conversion of CO 2 to methanol using a modified Cu/ZnO/Al 2 O 3 catalyst, Ma et al provided a short review on the formation of methanol from CO 2 by direct and indirect hydrogenation pathways, Gonzalez-Velasco et al investigated kinetics, model discrimination, and parameters of CO 2 methanation, Ding et al and Benito et al studied the mechanism of CO 2 methanation and promoter effect on the catalyst performance. For the transformation of CO 2 using chemicals other than green hydrogen, Ateka et al reported the joint conversion of CO 2 with syngas to synthesize light olefins, Liang et al and Sun et al prepared nickel-based catalysts for CO 2 reforming of methane, Jin et al investigated carbon fixation via the gasification of polypropylene and polycarbonate in a CO 2 environment, Song et al revealed mechanistic insights into the promotional effect of CO 2 on propane aromatization, and Liu et al reported enhanced CO 2 decomposition via frosted dielectric barrier discharge plasma .…”
mentioning
confidence: 99%